2018
DOI: 10.31584/jhsmr.v36i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Thai Adolescent Depression: Recurrence Prevention in Practice

Abstract: This article aims to review the current practice of recurrence prevention and intervention of adolescent depressive disorder in Thailand. In particular, we assess the Clinical Practice Guideline of Major Depressive Disorder for General Practitioners (CPG-MDD-GP) for Thailand, which is now the official guideline for all depressive patients who are children, adolescents, and adults in Thailand. Although this current Thai clinical guideline was developed and derived from the National Institute for Health and Care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Depression and anxiety disorder are common and profoundly affect the quality of life. 1 HIV infection may be a cause or consequence of mental health difficulties. Despite the availability of effective antiviral treatments (ART), mental health is an important factor that affects antiretroviral treatment compliance and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety disorder are common and profoundly affect the quality of life. 1 HIV infection may be a cause or consequence of mental health difficulties. Despite the availability of effective antiviral treatments (ART), mental health is an important factor that affects antiretroviral treatment compliance and patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with depression could be among those classified in this study as “no depressed mood”, and vice versa. The use of both PHQ-2 items could further improve the positive predictive value of the assessment[25] and should be considered for future studies on depression among Thai adolescents[33]. Furthermore, measurement of binge-drinking was defined by number of drinks per one "typical" drinking session during the past month, and not the more common definition of whether a participant had consumed 5 or more standard drinks in one session at any point within the past month[34], affecting the comparability of our study findings with regard to the association between binge-drinking and possible depression.…”
Section: Discussionmentioning
confidence: 99%
“…The United States Preventive Services Task Force, and The National Institute for Health and Care Excellence of the United Kingdom, advises that routine depression screening in primary health care be done to assist accurate diagnose, effective treat and monitoring of depression. 21,22 In a study of the Indonesian population, in 2021, it was concluded that it was highly crucial to recognize and prevent depression in primary health care at an early stage. 23 The Beck Depression Inventory, the 20-item Center for Epidemiological Studies Depression Scale (CES-D), the 9-item Patient Health Questionnaire (PHQ-9), the Quick Inventory of Depressive Symptomatology-Self-Records (QIDS-SR), and The Depression, Anxiety, and Stress Scale (DASS-21) are some major instruments used for depression screening.…”
Section: Depression Management In Primary Health Carementioning
confidence: 99%